An Estimate of Nickel Solubility in Industrial Slags - Biswas AK (The Australasian Institute of Mining and Metallurgy, 1975)
The solubility of nickel in matte smelt- ing slags, both as oxide and in the metallic form, is predicted using the results of a recent experimental work carried out with lime- free iron silicate slags as well as slags containing lime. Predicted solubilities are much lower than the nickel content of smelting slags, indicating that entrapped and possibly dissolved matte could be the major cause of nickel losses in such slags.